FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN LESI PRA KANKER - Enggoa, Ferdianti; Ratna Dewi, Rachmawati, (JURNAL MEDIA KESEHATAN, 2018)
The prevalence of cervical cancer in Indonesia is estimated in every day that41 new cases of cervical cancer and about 20 people every day die. Bengkulu provinceranked fourth with a prevalence of cancer of 1.9% with the total number of cervicalcancer patients in 2015 as many as 705 cases. Early detection of pre-cancerous lesionsthrough IVA test. Factors affecting pre-cancerous lesions consist of marital age, age,parity and hormonal contraceptive use. The purpose of this research is to know the factorsthat influence the incidence of pre-cancer lesions in the Region of Puskesmas CareKembang Seri Talang Empat Sub-district, Central Bengkulu Regency Year 2017. Thisresearch is analytical descriptive research with case control design. Samples A case groupof women with positive IVA test results of 36 people with total sampling technique andwomen's control group with negative IVA test results with a 1: 1 comparison was takenwith a simple random technique. Data were analyzed using Chi-Square test and BinaryLogistic Regression. The results showed that nearly half of the respondents had positivepre-cancerous lesions, mostly married ≤20 years, most of the use of hormonalcontraceptives ≥5 know, most respondents were mother's age> 35 years and mostly.There is a relationship of married age, the use of hormonal contraceptives and parity tothe incidence of pre-cervical cancer lesions and no relationship of maternal age with theincidence of cervical pre-cancer lesions The most influential factor on the incidence ofpre-cancerous lesions is married age. It is hoped that Puskesmas should be able tocoordinate and cooperate with cross-sectional about the age of menikha that must be doneat age> 20 years and do ekrjasama with school parties to prevent teenage pregnancy bydoing cooperation with organization of PIK-R.